THE EFFECT OF COMPENSATION, MOTIVATION AND ORGANIZATIONAL COMMITMENT ON THE PERFORMANCE OF EMPLOYEES AT PT. BRIDGESTONE SUMATRA RUBBER ESTATE - Chrisanti, Chrisanti; Chandra, Vanessa; Yunior, Khomeiny (RADJA PUBLIKA, 2022)
This study aims to determine and analyze the effect of compensation, motivation and organizational commitment on employee performance at PT. Bridgestone Sumatra Rubber Estate. In the problems that occur in PT. Bridgestone Sumatera Rubber Estate declining sales and the effects of the pandemic which resulted in a decrease in employee performance. On compensation in PT. Bridgestone Sumatra Rubber Estate is the lack of compensation provided by the company. Problems that occur in PT. Bridgestone Sumatra Rubber Estate lacks the company's attention to the work motivation of the company's leadership by providing motivation to encourage employees to work diligently, and discipline in working so as to improve employee performance. Problems that occur in PT. Bridgestone Sumatra Rubber Estate lacks commitment to employees in the empowerment of its employees in the form of self-confidence which results in a decrease in organizational commitment. The research approach used is a quantitative approach. The sampling method uses a simple random sampling technique. The sample of this study is the entirety of PT. Bridgestone Sumatra Rubber Estate as many as 109 people. The type of research used in this study is quantitative descriptive research. The nature of the research used is explanatory research. The statistical method uses multiple linear regression analysis, with hypothesis testing statistical test t. And the results of this study show that compensation, motivation and organizational commitment simultaneously affect employee performance at PT. Bridgestone Sumatra Rubber Estate. Compensation has a partial and significant effect on the performance of employees at PT. Bridgestone Sumatra Rubber Estate. Motivation has a partial and significant effect on employee performance at PT. Bridgestone Sumatra Rubber Estate. Organizational commitment has no effect and is partially significant to the performance of employees at PT. Bridgestone Sumatra Rubber Estate.